(untitled) (Web of Teachers: Inderscience Research, 2025)
This scientific article discusses the socio-pedagogical foundations of the formation of tolerance traits through the organization of children’s activities in preschool educational organizations based on development centers. The study scientifically and theoretically analyzes the essence of the concept of tolerance, its role in the personal development of preschool children, the educational capabilities of development centers, and the importance of pedagogical activity. It is also substantiated that cooperative activities organized in development centers serve to develop tolerance, empathy, mutual respect, and social adaptation skills in children.